Layer-like FAU-type zeolites: A comparative view on different preparation routes - Reiprich, Bastian; Weissenberger, Tobias; Schwieger, Wilhelm; Inayat, Alexandra (Frontiers of Chemical Science and Engineering, 2020)
The creation of intergrown layer-like zeolite crystals is one route to form hierarchical zeolites. Faujasite-type (FAU-type) zeolites are among the industrially most important zeolites and the implementation of hierarchical porosity is a promising way to optimise their catalytic and adsorptive performance. After a short general survey into routes for the preparation of hierarchical pore systems in FAU, we will review the currently existing strategies for the synthesis of FAU with layer-like morphology. Those strategies are mainly based on the presence of morphology modifying agents in the synthesis mixture. However, a very recent approach is the synthesis of layer-like FAU-type zeolite crystals assembled in an intergrown manner in the absence of such additives, just by finely adjusting the crystallization temperature. This additive-free preparation route for layer-like FAU, which appears very attractive from an ecological as well as economic point of view, is highlighted in this review. Concluding, a comparison, including powder X-ray diffraction, scanning and transmission electron microscopy, nitrogen physisorption and elemental analysis, between conventional FAU and three layer-like FAU obtained by different synthesis routes was carried out to show the structural, morphological and textural differences and similarities of these materials. [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2020-01-21
Keywords: FAU; hierarchical zeolite; layer-like morphology